SLRV: An RFID Mutual Authentication Protocol Conforming to EPC Generation-2 Standard - Mu’awya Naser; Ismat Aldmour; Rahmat Budiarto; Pedro Peris-Lopez (Universitas Ahmad Dahlan, 2015)
Having done an analysis on the security vulnerabilities of Radio Frequency Identification (RFID) through a desynchronization and an impersonation attacks, it is revealed that the secret information (i.e.: secret key and static identifier) shared between the tag and the reader is unnecessary. To overcome the vulnerability, this paper introduces Shelled Lightweight Random Value (SLRV) protocol; a mutual authentication protocol with high-security potentials conforming to electronic product code (EPC) Class-1 Generation-2 Tags, based on lightweight and standard cryptography on the tag’s and reader’s side, respectively. SLRV prunes de-synchronization attacks where the updating of internal values is only executed on the tag’s side and is a condition to a successful mutual authentication. Results of security analysis of SLRV, and comparison with existing protocols, are presented.